2015
DOI: 10.1080/00987913.2015.1035991
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of RDS on Usage of Electronic Content in UK Academic Libraries: Selected Results from a UKSG-Funded Project

Abstract: Citation: SPEZI, V., CREASER, C., CONYERS, A., 2015 Abstract (100 words)Resource Discovery Services (RDS), also called Web-scale Discovery Services, have attracted considerable attention in recent years. This article aims to provide an environmental scan of the adoption of RDS in UK higher education libraries and provide an analysis of RDS resource usage data to gauge whether RDS have an impact on the overall usage of e-journals and e-books. Findings show that there appears to be a positive impact in most cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Niu et al (2010) argue that the fact that the use of library interfaces figures so highly in researchers' information-seeking strategies may be explained by libraries' effort across the world in recent years to implement metasearch tools, making it easier for users to search across different platforms and resources, as well as a more general effort to support Google-like search tools featuring natural language searching. Those efforts to integrate meta-searching and Google-like search boxes in a user-friendly platform are embodied in the growing use of Web-scale discovery services in higher education libraries (Spezi et al 2015). As pointed out by Niu et al (2010), seeing library interfaces figuring neck to neck with Web searching in the top ranked searching tools is of notable importance, not the least because it provides strong evidence that academic searching is not only done through Web search engines, as commonly suggested in the literature.…”
Section: Where Do They Start and Why?mentioning
confidence: 99%
“…Niu et al (2010) argue that the fact that the use of library interfaces figures so highly in researchers' information-seeking strategies may be explained by libraries' effort across the world in recent years to implement metasearch tools, making it easier for users to search across different platforms and resources, as well as a more general effort to support Google-like search tools featuring natural language searching. Those efforts to integrate meta-searching and Google-like search boxes in a user-friendly platform are embodied in the growing use of Web-scale discovery services in higher education libraries (Spezi et al 2015). As pointed out by Niu et al (2010), seeing library interfaces figuring neck to neck with Web searching in the top ranked searching tools is of notable importance, not the least because it provides strong evidence that academic searching is not only done through Web search engines, as commonly suggested in the literature.…”
Section: Where Do They Start and Why?mentioning
confidence: 99%
“…Wolff, Rod, and Schonfeld (2016), in the Ithaka longitudinal series of studies, show web search engines to have been the primary route for search since 2010, and that continues today. Spezi, Creaser, and Conyers (2015) and funded by UKSG showed that almost all UK universities have now implemented a library discovery engine, and the same would be true in the USA. Moreover, more recently, they have started to be deployed in public libraries (see, e.g.…”
Section: Library Discovery Systemsmentioning
confidence: 90%
“…Such systems effectively consolidate all resource indexes (including, if required, the catalogue, institutional repositories, and any other data set deemed useful) into one search portal. Research undertaken by Spezi, Creaser, and Conyers () and funded by UKSG showed that almost all UK universities have now implemented a library discovery engine, and the same would be true in the USA. Moreover, more recently, they have started to be deployed in public libraries (see, e.g.…”
Section: Library Discovery Systemsmentioning
confidence: 97%
“…19-20) The UKSG, a library group in the United Kingdom (UK), distributed a survey to UK higher education institutions to solicit information and opinions about web-scale discovery service adoption and its impact on electronic usage. The survey was accompanied by case studies on electronic usage as well as interviews with stakeholders to unearth opinions and insights regarding web-scale discovery services (Spezi et al, 2013(Spezi et al, , 2015. The authors found that adoption rates were relatively high, with 48 out of 62 respondent libraries (77%) having implemented a web-scale discovery service.…”
Section: Literature Reviewmentioning
confidence: 99%